SOSIALISASI POLITIK PASANGAN CALON GUBERNUR DAN WAKIL GUBERNUR MELALUI ALAT PERAGA KAMPANYE DAN BAHAN KAMPANYE OLEH KOMISI PEMILIHAN UMUM PROVINSI SULAWESI UTARA - Budiawan, Eka (JURNAL POLITICO, 2017)
AbstractThe low level of voters’ participation in the 2015 gubernatorial election in North Sulawesi Province showed that the candidates’ political socialization done by the local electoral commission was looked not work well. The local electoral commission had attempted to introduce the candidate but the level of public participation in the election was still low. Thus, it is necessary to find a way out through research.From the research, it can be informed that the political socialization was implemented the local electoral commission based on the regulation. The materials of political socialization including banners and billboards were not the cause of the low level of public participation in the election. They help the voters to know the candidates’ vision, mission and program. But they were not able to encourage the voters to vote. The voters’ preferences were determined by the regional representation of the candidates. The patern of socialization and the placement of campaign props during campaign period were done through coordination with the local governments. The spread of campaign materials were done by the candidates’ campaign teams to the people.Keywords : Political Socialization, Campaign Props, Campaign Materials.